Raman Spectroscopy as Spectral Tool for Assessing the Degree of Conversion after Curing of Two Resin-Based Materials Used in Restorative Dentistry - Eduard Gatin; Stefan-Marian Iordache; Elena Matei; Catalin-Romeo Luculescu; Ana-Maria Iordache; Cristiana Eugenia Ana Grigorescu; Roxana Romanita Ilici (Diagnostics, 2022)
(1) Background: The treatment of dental cavities and restoration of tooth shape requires specialized materials with specific clinical properties, including being easy to model, light-cured, having a natural color, reduced shrinkage, a hardness similar to hydroxyapatite, and no leakage. The dimensional stability of resin composite materials is affected by polymerization shrinkage, degree of conversion (number of π carbon bonds converted into σ ones), thermal contraction and expansion, and interactions with an aqueous environment. (2) Methods: The materials used in our investigation were two composite resins with similar polymer matrices, but different filler (micro/nano filler). To evaluate the properties of samples, we employed the pycnometer technique (pycnometer from Paul Marienfeld Gmbh, Lauda-Königshofen, Germany), RAMAN spectroscopy technique (MiniRam Equipment from B&W Tek Inc., Plainsboro Township, NJ, USA; 785 nm laser source), SEM and EDX (FEI Inspect S.). (3) Results: The size of the filler plays an important role in the polymerization: for the pycnometric results, the larger particle filler (Sample 1) seems to undergo a rapid polymerization during the 45 s curing, while the nanoparticle filer (Sample 2) needs additional curing time to fully polymerize. This is related to a much larger porosity, as proved by SEM images. The lower degree of conversion, as obtained by Raman spectroscopy, in the same geometry means that the same volume is probed for both samples, but Sample 1 is more porous, which means less amount of polymer is probed for Sample 1. (4) Conclusions: For the two composites, we obtained a degree of conversion of 59% for Sample 1 and 93% for Sample 2, after 45 s of curing.